Gender and Sexuality Issues in Indian Literatures: Exploring the Intersection of Gender, Sexuality, and Literature in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Gender and sexuality are the two broadly utilized terms in the feminist abstract feedback. The expression gender has been utilized since mid-1970s to mean socially built femininity and masculinity rather than natural sex contrasts. Though the words sexuality and sex allude to the natural sexual divisions into male and female and which includes sensual joy, exercises, yearning and personalities.Sociologically gender is defined as the socio-social definition of men and ladies, the way social orders distinguish men and ladies and allocate them social parts.Gender assumes a key part in forming individual personality, self-discernment and impression of others by us or of us by them. Since it is joined to the organic sex it ascribes the qualities to the separate sex and the females are viewed as feminine and males are masculine.